2021
DOI: 10.7575/aiac.ijels.v.9n.1p.124
|View full text |Cite
|
Sign up to set email alerts
|

Wattpad in Youth Literature Based on the Experiences of Turkish Teachers and Secondary School Students

Abstract: This study aims to discover the view, opinion, perception and experiences of Turkish teachers and secondary school students towards Wattpad, an online literacy community, to interpret them educationally, to determine the reasons for their use and to interpret the main plot of youth literature on the axis of changing reading perception/behavior and expectations of youth. It is foreseen that the study has comparatively discussed literature-education and new reading types on the axis of the teacher and student, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Besides, this study also revealed the weaknesses of using Wattpad for performing extensive reading based on the students' perceptions, which were similarities in the reading materials that sometimes make them boring to read, tired eyes, distractions from the other notifications, and battery power-draining (Permatasari et al, 2020). Besides, a previous study conducted by Başoğul (2021) revealed that Turkish secondary school students enjoyed spending their time on Wattpad because they argued that Wattpad could develop their reading and writing habits as well as give comments and criticize books/articles with their peers, so that they liked digital reading through Wattpad (Başoğul, 2021). However, this study also revealed that the teachers argued that the students had to utilize Wattpad carefully for digital reading because it might include violence, sexuality, and other inappropriate contents (Başoğul, 2021).…”
Section: Digital Extensive Reading Through Wattpadmentioning
confidence: 68%
See 1 more Smart Citation
“…Besides, this study also revealed the weaknesses of using Wattpad for performing extensive reading based on the students' perceptions, which were similarities in the reading materials that sometimes make them boring to read, tired eyes, distractions from the other notifications, and battery power-draining (Permatasari et al, 2020). Besides, a previous study conducted by Başoğul (2021) revealed that Turkish secondary school students enjoyed spending their time on Wattpad because they argued that Wattpad could develop their reading and writing habits as well as give comments and criticize books/articles with their peers, so that they liked digital reading through Wattpad (Başoğul, 2021). However, this study also revealed that the teachers argued that the students had to utilize Wattpad carefully for digital reading because it might include violence, sexuality, and other inappropriate contents (Başoğul, 2021).…”
Section: Digital Extensive Reading Through Wattpadmentioning
confidence: 68%
“…Besides, a previous study conducted by Başoğul (2021) revealed that Turkish secondary school students enjoyed spending their time on Wattpad because they argued that Wattpad could develop their reading and writing habits as well as give comments and criticize books/articles with their peers, so that they liked digital reading through Wattpad (Başoğul, 2021). However, this study also revealed that the teachers argued that the students had to utilize Wattpad carefully for digital reading because it might include violence, sexuality, and other inappropriate contents (Başoğul, 2021). Besides, another similar study conducted by Sari (2022) revealed that many students believed that Wattpad could be used as a useful digital media because the students could read the collections of the digital stories through Wattpad (Sari, 2022).…”
Section: Digital Extensive Reading Through Wattpadmentioning
confidence: 97%
“…In her doctoral thesis, Sivri (2021) evaluated Turkish Wattpad novels with the method of feminist literary criticism and evaluated the texts produced by conservative young women and the reader comments on these texts while deconstructing the hegemonic masculinity and accentuated femininity produced in this new subculture. Başoğul (2021), in her study, interpreted the opinions of Turkish teachers and secondary school students about Wattpad. According to the results obtained in the study, it was seen that 7 th and 8 th grade students among secondary school students use Wattpad more and prefer to use this application from the mobile environment.…”
Section: Literature Surveymentioning
confidence: 99%
“…According to the results obtained in the study, it was seen that 7 th and 8 th grade students among secondary school students use Wattpad more and prefer to use this application from the mobile environment. According to the general view of Turkish teachers, it has been learned that students with low academic success and family problems use this application to be popular and attract attention among their peers (Başoğul, 2021). Acar et al (2021) examining the fifteen completed Turkish books that reached 150,000 or more likes in the ChickLit (young woman's literature) category on Wattpad platform, revealed that the books have content features of sexually explicit behaviors; such as, unhealthy family representations, representations of men and women, in which gender characteristics are emphasized, risky behaviors; such as, substance use, crime, violence, suicide, sexual intercourse at an early age, pornographic presentations, and rape.…”
Section: Literature Surveymentioning
confidence: 99%
“…Independent reading and writing activities on Wattpad are perceived as calming and amusing by secondary school pupils. In light of these findings, relevant educators should combine learning and teaching environments by developing various action plans based on students' in-class and out-of-class experiences, as well as their interests and requirement (Başoğul, 2021).…”
Section: Introductionmentioning
confidence: 99%